2018
DOI: 10.1063/1.5019255
|View full text |Cite
|
Sign up to set email alerts
|

Hot spots induced by LHCD in the shadow of antenna limiters in the EAST tokamak

Abstract: Hot spots induced by lower hybrid wave in experimental advanced superconducting tokamak tokamak have caused high performance experiment disruption and serious damages to the guard limiters. Experimental and theoretical analyses have been carried out to study its physical mechanism. Plasma density scan experiments indicate that the wall temperature within the hot spots enhanced by a factor of 5 and increases with the plasma density near the antenna. A lower hybrid current drive (LHCD)-only density climb experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Continuous growth of Z eff during the LHW ramping-up phase is most likely caused by the impurity sputtering from the interactions between ELMs and surface or the 'hotspot' often occurring in the case of high P LHW . [54] The increased C W after 6.2 s is due to tungsten droplet events. Using this droplet event, the tungsten confinement time is also evaluated to be about 68.5 ms.…”
Section: Impurity Confinement In Lhw and Ecrh Heated Small Elmy H-mod...mentioning
confidence: 98%
“…Continuous growth of Z eff during the LHW ramping-up phase is most likely caused by the impurity sputtering from the interactions between ELMs and surface or the 'hotspot' often occurring in the case of high P LHW . [54] The increased C W after 6.2 s is due to tungsten droplet events. Using this droplet event, the tungsten confinement time is also evaluated to be about 68.5 ms.…”
Section: Impurity Confinement In Lhw and Ecrh Heated Small Elmy H-mod...mentioning
confidence: 98%
“…Severe hotspot issues were observed in the 2016 EAST campaign with higher lower hybrid input power. The experi ments indicated that plasma disruptions happened at high plasma densities [9]. Unfortunately there were no direct meas urements of plasma density and electron temperature near the antenna in the 2016 campaign.…”
Section: Simulation Model and Setupmentioning
confidence: 98%
“…For EAST, there are two lower hybrid power systems with two frequencies at 2.45 GHz and 4.6 GHz, respectively. The incident powers for 2.45 GHz and 4.6 GHz systems are typically around 1 MW and 1.5 MW, and hotspots are often observed when the input power for 4.6 GHz is above 1.8 MW [8][9][10]. In this work, we focus on hotspots induced by 4.6 GHz LHW.…”
Section: Simulation Model and Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Hot spots induced by fast particles in EAST (experimental advanced superconducting tokamak) have been found to limit the improvement of the plasma performance (Li et al. 2018). The CX losses of NBI fast ions may produce hot spots in EAST.…”
Section: Introductionmentioning
confidence: 99%